The Effect of Storage Temperature and Packaging Method on the Shelf Life of Broccoli (Brassica oleracea L. var italica) - Lana E. Lalujan; Gregoria S. S. Djarkasi; Maria F. Sumual; Nurul ` Masloman (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2026)
This study is aimed to evaluate the most effective storage temperature conditions and packaging methods for maintaining broccoli's physical quality, including changes in weight, water content, texture, and color during storage. This study used a descriptive method with six treatments: a combination of three storage temperature (5°C, 19°C, and 27°C) and two packaging methods: plastic film wrapping (PFW) and vacuum packaging (VP), each were duplicated. The results showed that the 5°C temperature treatment with PFW provided the best results in maintaining broccoli's physical quality during 15 days of storage. This treatment showed a relatively low weight loss of 12.77%, stable moisture content ranging from 79.5% to 77%, and higher firmness retention, with a decrease in hardness from 237.68 N to 170.18 N. Color change was also slower than other treatments, with L*, a*, and b* values remaining within the range indicating a fresh green color. Meanwhile, treatments with higher storage temperatures, 19°C and 27°C, showed a rapid quality decline, in terms of weight loss, decrease in moisture content and hardness, and color change, especially in VP. Overall, the combination of a storage temperature of 5°C and the PFW method was the most effective treatment in extending the shelf life and maintaining the physical quality of broccoli. These findings highlight the importance of integrating temperature management and appropriate packaging strategies to extend the shelf life of broccoli during postharvest handling and distribution.